Unique types and innovation input of family firm CEOs: moderating role of managerial ability in Chinese listed firms - Sadeen Ghafoor; Weidong Huo; Man Wang; Yunjiang Geng; Muhammad Zulfiqar; Muhammad Usman Yousaf (Humanities & Social Sciences Communications, 2024)
Abstract In family firms the role of CEO is highly significant with reference to devise strategic decisions and deciding if it is feasible to invest in innovation input. This study aims to investigate the behaviour analyses of the diverse types of CEOs in family firms towards innovations. This study also analyzes the moderating role of managerial ability in the nexus of CEO types and innovation input. The data are obtained from Chinese A-share listed family firms from Accounting Research and China Stock Exchange in 2012–2020 and analysed using ordinary least squares regression. Tobit and probit regressions are also employed to confirm the results. Results indicate that non-family and family CEOs (with no controlling rights) show identical behaviour concerning their lower intentions to promote innovations in R&D projects than family CEOs with actual controlling rights. In addition, family CEOs with actual controlling rights exert a positive effect on R&D, indicating that they are more willing to invest in innovative projects. Moreover, we observe the significant moderating role of managerial ability in the nexus of CEO types and innovation activities. We find that high managerial ability alters the behaviour of different CEOs. With the moderation of managerial ability, non-family and family CEOs (without actual controlling rights) also show willingness to invest in innovative projects and without managerial ability, CEOs’ willingness to make innovations decline. This study is a pioneer work that investigates the impact of diverse types of CEOs to unlock notable insights regarding the R&D investment behaviour of Chinese family firms with moderating role of managerial ability. This study is useful to all parties involved with the company, including employees, clients, suppliers and customers. The results of this study can also assist board members in selecting and recruiting non-family CEOs or keeping family CEOs (with or without actual controlling rights).